Radiohead et le rock progressif : histoire d’un malentendu - Michel Delville (Revue LISA)
In the mid-1990s, Radiohead entered the restricted circle of rock bands whose ability to carry out the creative synthesis of their era has earned them the enviable status of experimental group worshipped by large audiences, like the Beatles or Pink Floyd, to which they are (too) often compared. Radiohead’s connections with progressive rock raise a number of basic issues about the genres, sources and influences of popular music, the relationship between mass and high culture, and the position occupied by so-called “alternative” groups on the pop-rock scene.